Avaliação da vida em fadiga em juntas de liga de alumínio AA 5052 soldadas por solda ponto por fricção - Bonamigo, Roberto (2021)
The fatigue process is due to cyclic loads applied to components, causing cracks in the material and thus causing the vast majority of failures and ruptures of the components. Even with all the technological progress, welded joints remain the critical point, susceptible to failure and fatigue defects. This job is intended for the analysis and evaluation of welded joints, using a method of unconventional welding, friction spot welding. It seeks to analyze life in fatigue of different joints, welded with different tool geometries, thus comparing their respective fatigue lives and mechanical properties for justify the use of the friction spot welding method as a method to welding. The material used was the light aluminum alloy AA 5052, which has a smaller weight and represents a high cost-benefit to industries in relation to other steels. First, three different tools were manufactured to carry out the welding, then friction spot welding was performed using the same welding parameters for all tools, after which bodies were prepared test for the assessment of fatigue life, using 50% of the maximum limit of flow of each welded joint and also a specimen, for each condition, for macrographic, micrographic and microhardness characterization of joints welded. Having carried out all stages of the work, with the results obtained, we sought to compare life in fatigue, where all joints obtained infinite life in fatigue, and the microhardness of the different welded joints to justify the use of friction spot welding in aluminum alloys as an improvement for industries.